High-toughness corrosion-resistant Cr-V series spring steel based on multi-element microelement coupling and preparation method of high-toughness corrosion-resistant Cr-V series spring steel

By using multivariate trace element coupling technology in spring steel, the chemical composition and process flow are optimized, and the problems of existing spring steel are easily corroded and high preparation costs in extreme environments are solved, achieving high strength, tough corrosion resistance and low cost. Comprehensive effect.

CN119433347APending Publication Date: 2025-02-14UNIV OF SCI & TECH BEIJING +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411537762.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing spring steels are prone to local corrosion in extreme service environments and have high preparation costs, making it difficult to meet the needs of high strength, corrosion resistance and low cost.

Method used

High-strength, tough corrosion-resistant Cr-V spring steel based on multivariate trace element coupling is used, and its chemical composition includes C 0.45-0.55%, Si 0.15-0.35%, Mn 0.60-0.90%, Cr 0.80-1.20%, V 0.06-0.26 % and other elements are prepared by combining thermodynamic analysis and adaptation of the trace element system and content in the steel with multivariate trace element coupling thermodynamic analysis and adaptation, and combined with casting, forging, quenching and tempering processes to prepare spring steel with high strength, toughness and corrosion resistance.

Benefits of technology

The corrosion resistance and hydrogen embrittlement resistance of spring steel are achieved, while reducing the preparation cost and improving the service performance of the material in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433347A_ABST
    Figure CN119433347A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of steel production and manufacturing, and discloses high-toughness corrosion-resistant Cr-V series spring steel based on multi-element trace element coupling and a preparation method thereof, the spring steel comprises the following components in percentage by mass: 0.45-0.55% of C, 0.15-0.35% of Si, 0.60-0.90% of Mn, 0.80-1.20% of Cr, 0.06-0.26% of V, 0.01-0.03% of Al, 0.015-0.025% of Ti, 0.0020-0.0055% of B, 0-0.02% of Nb, less than or equal to 0.025% of P, less than or equal to 0.025% of S, less than or equal to 0.2% of Cu, less than or equal to 0.3% of Ni, less than or equal to 0.008% of N, less than or equal to 0.0017% of impurities and the balance of Fe. The prepared spring steel has corrosion resistance and hydrogen embrittlement resistance and meanwhile has the characteristics of being low in cost, uniform in structure and excellent in hardenability and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel production and manufacturing, and in particular to a high-strength, toughness, and corrosion-resistant Cr-V series spring steel based on multi-element coupling and a preparation method thereof. Background Art

[0002] At present, the weather resistance of steel is usually achieved by adding a certain amount of expensive alloy elements such as Cr, Ni, and Mo. The key to its mechanism of action is to promote the formation of a dense oxide film on the surface of the substrate, thereby hindering the invasion of corrosive media. This method of improving weather resistance is reliable, but it also directly increases the cost of manufacturing. Spring steel is a special steel material widely used in the industrial field. It usually plays the role of absorbing energy, reducing vibration and impact. It often has to withstand various alternating stresses such as cyclic bending, tension, compression, and torsion, and the working conditions are very harsh. However, domestically produced spring steel products are prone to rust during export and shipping due to their lack of weather resistance, and are particularly sensitive to local corrosion in extreme service environments. Local corrosion in the material often occurs first at defects with higher energy, such as grain boundaries and dislocations. Certain harmful elements such as P and S that segregate at grain boundaries can easily have an adverse effect on corrosion resistance. The most direct way to solve this problem is to add appropriate elements that can preferentially segregate at grain boundaries but do not weaken grain boundaries to inhibit the segregation of harmful elements at grain boundaries. This study found that the cheap B element can meet this condition. At present, the commonly used spring steels such as 50CrVA and 60Si2Mn are not corrosion-resistant, which makes spring steel prone to rust during export sea transportation. In the long-distance transportation of export, sea transportation is the most convenient and economical mode of transportation. However, the marine atmosphere is highly corrosive, which makes the corrosion problem of spring steel more likely to occur. During the sea transportation process, the material will rust significantly, resulting in corrosion failure, which often causes quality disputes and causes economic losses.

[0003] In the prior art, the patent application number 201610955197.3 proposes a production process for black spring flat steel, the chemical composition (wt%) of which is: C 0.46-0.54%, Si 0.17-0.37%, Mn 0.60-0.80%, Cr 0.90-1.10%, V 0.10~0.20%, P≤0.025%, S≤0.025%, N≤0.008%, the rest are iron and other inevitable impurities, the rolling temperature is 1000~1050℃, the final rolling temperature is 950~1000℃, the upper cooling bed temperature is 850~900℃, the large shear temperature is 250~400℃, the packaging temperature is 50~150℃, and the temperature range from 530~570℃ after the upper cooling bed is cooled by fast cooling (≤60℃ / min), and after 530℃, slow cooling (≤30℃ / min) is used. In this way, a dense and continuous ferroferric oxide scale can be formed on the surface of the spring steel to avoid environmental corrosion during transportation.

[0004] The patent with application number 202210097677.6 proposes a method for changing the composition to improve the corrosion resistance of spring steel. Its composition, by weight percentage, is C 0.38~0.48, Si 2.20~2.30, Mn0.63~0.75, P≤0.010, S≤0.0030, Cr 0.72~0.79, Ni 0.35~0.40, Nb 0.05~0.07, Re 0.022~0.028, and the balance is Fe and unavoidable impurities. By appropriately reducing the carbon content and increasing the trace elements Ni, Nb and Re, without using aluminum deoxidizer throughout the process, using ferrosilicon alloys and some rare earth alloys as well as ferrochrome alloys for deoxidation and alloying during the converter steelmaking process, adding nickel iron and niobium iron for alloying in the LF refining process, and combining the quenching and tempering heat treatment process, the prepared high-strength spring steel has good corrosion resistance and outstanding mechanical properties.

[0005] However, under the international background of carbon peak and carbon neutrality development requirements, special spring steel will gradually develop in the direction of high strength, toughness, light weight and long service life. However, the preparation cost of high strength, toughness and corrosion-resistant spring steel in the existing technology is too high. If the cost is reduced, the comprehensive performance of the spring steel will be reduced.

[0006] Therefore, it is of great significance to study a Cr-V spring steel with high toughness and corrosion resistance based on the coupling of multiple trace elements and a low-cost preparation method. Summary of the invention

[0007] In view of this, the present invention provides a high-strength, toughness, corrosion-resistant Cr-V series spring steel based on multi-element coupling and a preparation method thereof, the purpose of which is to solve the problems of poor corrosion resistance, high production cost and weak hydrogen embrittlement resistance of existing spring steel.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] The invention provides a high-strength, tough and corrosion-resistant Cr-V series spring steel based on multi-element coupling, comprising the following components by mass fraction: C 0.45-0.55%, Si 0.15-0.35%, Mn 0.60-0.90%, Cr 0.80-1.20%, V 0.06-0.26%, Al 0.01-0.03%, Ti 0.015-0.025%, B 0.0020-0.0055%, Nb 0-0.02%, P≤0.025%, S≤0.025%, Cu≤0.2%, Ni≤0.3%, N≤0.008%, impurities≤0.0017%, and the rest is Fe.

[0010] The present invention also provides a method for preparing the high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling, comprising the following steps:

[0011] Firstly, through multi-element coupled thermodynamic analysis, the trace element system and content in the steel are adaptively designed, and the metal blocks corresponding to the above elements are smelted in the order of C, Si, Mn, Cr, V, Al, Ti, B, Nb, P, S, Cu, Ni, N and Fe, and then cast, forged, quenched and tempered in sequence to obtain high-strength, toughness and corrosion-resistant Cr-V spring steel.

[0012] Preferably, the smelting temperature is 1600-1700° C., and the smelting time is 80-100 min.

[0013] Preferably, the forging temperature is 950-1000° C., the forging time is 15-25 min, and the total forging deformation is 5-9%.

[0014] Preferably, the quenching temperature is 850-950° C., and the quenching medium is water or oil.

[0015] Preferably, the tempering temperature is 450-550° C., and the tempering time is 80-100 min.

[0016] Preferably, the plastic extension strength R of the obtained high-toughness and corrosion-resistant Cr-V spring steel is p0.2 ≥1250MPa, tensile strength R m ≥1300MPa, elongation after fracture A≥10%, end quenching index J≥48HRC / 30, impact energy≥30J.

[0017] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The spring steel prepared by the present invention has the characteristics of corrosion resistance and hydrogen embrittlement resistance, and at the same time has the characteristics of low cost, uniform structure, excellent hardenability and mechanical properties, which can effectively improve the service performance of spring steel in extremely complex use environments;

[0019] (2) The preparation process of the present invention is suitable for popularization and application by adapting and designing the trace element system and content through multi-element coupled thermodynamic analysis, thereby optimizing the production process, reducing the production cost and simplifying the process flow. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0021] Figure 1 The variation law of the solid solution amount of different trace elements in the high-strength, toughness and corrosion-resistant Cr-V series spring steel prepared by the present invention with temperature;

[0022] Figure 2 This is a comparison diagram of the potentiodynamic polarization of the spring steel materials obtained in Example 1 and Comparative Example 1;

[0023] Figure 3 This is a comparison diagram of the open circuit potential of the spring steel materials obtained in Example 1 and Comparative Example 1;

[0024] Figure 4 This is a comparison diagram of the potentiodynamic polarization of the spring steel materials obtained in Example 2 and Comparative Example 2;

[0025] Figure 5 This is a comparison diagram of the open circuit potential of the spring steel materials obtained in Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0026] The invention provides a high-strength, tough and corrosion-resistant Cr-V series spring steel based on multi-element coupling, comprising the following components by mass fraction: C 0.45-0.55%, Si 0.15-0.35%, Mn 0.60-0.90%, Cr 0.80-1.20%, V 0.06-0.26%, Al 0.01-0.03%, Ti 0.015-0.025%, B 0.0020-0.0055%, Nb 0-0.02%, P≤0.025%, S≤0.025%, Cu≤0.2%, Ni≤0.3%, N≤0.008%, impurities≤0.0017%, and the rest is Fe.

[0027] In the present invention, the mass fraction of C is preferably 0.47-0.53%, more preferably 0.48-0.52%, more preferably 0.5-0.51%, the mass fraction of Si is preferably 0.18-0.3%, more preferably 0.2-0.28%, more preferably 0.22-0.26%, the mass fraction of Mn is preferably 0.65-0.85%, more preferably 0.7-0.8%, more preferably 0.75-0.78%, the mass fraction of Cr is preferably 0.85-1.15%, more preferably 0.9-1.1%, more preferably 0.95-1%, the mass fraction of V is preferably 0.12-0.22%, and further preferably 0. The mass fraction of Al is preferably 0.015-0.025%, more preferably 0.018-0.022%, more preferably 0.02%, the mass fraction of Ti is preferably 0.018-0.024%, more preferably 0.019-0.023%, more preferably 0.02-0.022%, the mass fraction of B is preferably 0.0025-0.005%, more preferably 0.003-0.0045%, more preferably 0.0035-0.004%, the mass fraction of Nb is preferably 0.005-0.015%, more preferably 0 0.008~0.014%, more preferably 0.01~0.012%, the mass fraction of P is preferably 0.01~0.02%, more preferably 0.012~0.018%, more preferably 0.014~0.016%, the mass fraction of S is preferably 0.01~0.02%, more preferably 0.012~0.018%, more preferably 0.014~0.016%, the mass fraction of Cu is preferably 0.05~0.16%, more preferably 0.08~0.14%, more preferably 0.1~0.12%, the mass fraction of Ni is preferably 0.05~0.25%, more preferably 0.1~0.2%, more preferably The mass fraction of N is preferably 0.001-0.007%, more preferably 0.002-0.006%, more preferably 0.003-0.005%, the impurities are preferably ≤0.0003-0.0015%, more preferably 0.0007-0.0012%, more preferably 0.0009-0.0011%, and the rest is Fe; in the present invention, the impurities are preferably H and O, the mass fraction of H is preferably ≤0.0002%, more preferably ≤0.0001%, the mass fraction of O is preferably ≤0.0015%, more preferably ≤0.0012%, more preferably ≤0.0008%.

[0028] In the present invention, it is ensured that part of the B element exists in the form of a solid solution element inside the spring steel material, and only a trace amount of the B element can significantly improve the corrosion resistance of the spring steel material by enhancing the stability of the grain boundaries. The main function of the B element is to replace certain harmful elements that precipitate at the grain boundaries, thereby reducing the electrochemical activity at the grain boundaries. Compared with expensive corrosion-resistant alloying elements such as Cr, Ni, and Mo, the B element has more significant economic benefits. In addition, the trace amount of the B element can greatly improve the hardenability of the spring steel material, which is of great significance to the uniformity of the organization and performance of large-size structural spring steel parts and the low heat treatment distortion of precision parts.

[0029] In the present invention, the primary purpose of adding the Ti element is to fix nitrogen. Since the chemical properties of B element are active, it is very easy to be oxidized and nitrided. Once B forms a compound, its beneficial effect on corrosion resistance and hardenability will be significantly reduced. In addition, trace Ti elements can form dispersed nano-scale carbonitrides. These nanoparticles will act as deep hydrogen traps to effectively reduce the diffusion capacity of free hydrogen in the spring steel material, thereby significantly improving the hydrogen embrittlement resistance of the spring steel material.

[0030] In the present invention, the Nb is a strong carbon and nitride forming element, which can form an in-situ nano-precipitation phase to refine the grains and thus improve the strength and plasticity of the spring steel material. In addition, Nb carbides have been proven to be effective deep hydrogen traps, which can significantly reduce the hydrogen embrittlement sensitivity of the spring steel material.

[0031] In the present invention, the main purpose of adding Al in the smelting is deoxidation. Since B is an active element and is easily oxidized and nitrided, Ti must be used for nitrogen fixation and Al must be used for deoxidation before adding B element to avoid B being reacted to form compounds. If too much Al is added, brittle aluminum oxide inclusions may be formed, thereby reducing the toughness of the spring steel material.

[0032] The present invention also provides a method for preparing the high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling, comprising the following steps:

[0033] Firstly, through multi-element coupled thermodynamic analysis, the trace element system and content in the steel are adaptively designed, and the metal blocks corresponding to the above elements are smelted in the order of C, Si, Mn, Cr, V, Al, Ti, B, Nb, P, S, Cu, Ni, N and Fe, and then cast, forged, quenched and tempered in sequence to obtain high-strength, toughness and corrosion-resistant Cr-V spring steel.

[0034] In the present invention, the preparation method of high-strength, toughness and corrosion-resistant Cr-V series spring steel based on multi-element coupling includes multi-element coupling thermodynamic analysis, trace element adaptation design and process optimization.

[0035] In the present invention, the smelting temperature is preferably 1600-1700°C, more preferably 1620-1680°C, more preferably 1640-1660°C, and the smelting time is preferably 80-100 min, more preferably 85-95 min, more preferably 90-92 min.

[0036] In the present invention, the forging temperature is preferably 950-1000°C, more preferably 960-990°C, and more preferably 970-980°C. The forging time is preferably 15-25 min, more preferably 17-23 min, and more preferably 19-21 min. The total deformation of the forging is preferably 5-9%, more preferably 6-8%, and more preferably 7%.

[0037] In the present invention, the purpose of forging is to eliminate the defects of the as-cast structure and optimize the microstructure.

[0038] In the present invention, the quenching temperature is preferably 850 to 950° C., more preferably 870 to 930° C., and even more preferably 890 to 910° C., and the quenching medium is preferably water or oil.

[0039] In the present invention, the tempering temperature is preferably 450-550° C., more preferably 470-530° C., more preferably 490-510° C., and the tempering time is preferably 80-100 min, more preferably 85-95 min, more preferably 88-90 min.

[0040] In the present invention, the plastic extension strength R p0.2 ≥1250MPa, tensile strength R m ≥1300MPa, elongation after fracture A≥10%, end quenching index J≥48HRC / 30, impact energy≥30J.

[0041] The present invention adapts and designs the multi-element trace elements such as B, Nb, Ti, V, Al, etc. in the steel through thermodynamic coupling analysis, and combines the processing technology of the present invention to ensure that the trace solid solution boron element exists in the spring steel, which can effectively improve the corrosion resistance and hardenability of the spring steel material at the same time; secondly, the multi-element trace elements such as Ti, Nb, V, etc. form dispersed nanocarbonitrides in the spring steel material, which can inhibit the free diffusion of hydrogen inside the material. The multi-element nanocarbonitrides combined with the solid solution boron element at the grain boundary can also improve the impact work of the spring steel, and prepare a high-strength and corrosion-resistant spring steel with a dispersed multi-element nanophase.

[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0043] Example 1

[0044] In this embodiment, the mass fraction of each component is as follows:

[0045] C 0.49%, Si 0.3%, Mn 0.71%, Cr 0.98%, V 0.14%, Al 0.023%, Ti 0.018%, B 0.0036%, impurities 0.0015% (including H 0.0002%, O 0.0013%), and the rest is Fe element;

[0046] The metal blocks corresponding to C, Si, Mn, Cr, V, Al, Ti, B and Fe are sequentially added into a smelting furnace at 1640°C in the above order and according to the mass fraction of the above components for smelting for 90 minutes. After smelting, the alloy blocks are cast to obtain alloy blocks. The obtained alloy blocks are forged at a temperature of 980°C for 20 minutes, so that the total deformation is 9%. Subsequently, the forged alloy blocks are cooled to 850°C and quenched in oil. After quenching, they are tempered at 500°C for 90 minutes to obtain high-strength, toughness and corrosion-resistant Cr-V spring steel, which is recorded as "50CrTiNbVBA-1".

[0047] Example 2

[0048] In this embodiment, the mass fraction of each component is as follows:

[0049] C 0.51%, Si 0.32%, Mn 0.73%, Cr 0.99%, V 0.15%, Al 0.02%, Ti 0.019%, B 0.0031%, impurities 0.0014% (including H 0.0002%, O 0.0012%), and the rest is Fe element;

[0050] The metal blocks corresponding to C, Si, Mn, Cr, V, Al, Ti, B and Fe are sequentially added into a smelting furnace at 1640°C in the above order and according to the mass fraction of the above components for smelting for 85 minutes. After smelting, the alloy blocks are cast to obtain alloy blocks. The obtained alloy blocks are forged at a temperature of 980°C for 20 minutes, so that the total deformation is 8%. Subsequently, the forged alloy blocks are cooled to 850°C and quenched in oil. After quenching, they are tempered at 450°C for 100 minutes to obtain high-strength, toughness and corrosion-resistant Cr-V spring steel, which is recorded as "50CrTiNbVBA-2".

[0051] Example 3

[0052] In this embodiment, the mass fraction of each component is as follows:

[0053] C 0.51%, Si 0.32%, Mn 0.73%, Cr 0.99%, V 0.15%, Al 0.02%, Ti 0.019%, B 0.0031%, Nb 0.02%, P 0.025%, S 0.025%, Cu 0.2%, Ni 0.3%, N 0.008%, impurities 0.0015% (including H 0.0002%, O 0.0013%), the rest is Fe element;

[0054] The metal blocks corresponding to C, Si, Mn, Cr, V, Al, Ti, B, Nb, P, S, Cu, Ni, N and Fe are sequentially added into a smelting furnace at 1640°C in the above order and according to the mass fraction of the above components for smelting for 90 minutes. After smelting, the alloy blocks are cast to obtain alloy blocks. The obtained alloy blocks are forged at a temperature of 980°C for 20 minutes, so that the total deformation is 8%. Subsequently, the forged alloy blocks are cooled to 850°C and quenched in oil. After quenching, they are tempered at 450°C for 100 minutes to obtain high-strength, toughness and corrosion-resistant Cr-V spring steel, which is recorded as "50CrTiNbVBA-3".

[0055] Comparative Example 1

[0056] The “C 0.49%, Si 0.3%, Mn 0.71%, Cr 0.98%, V 0.14%, Al 0.023%, Ti 0.018%, B 0.0036%, impurities 0.0015% (including H 0.0002%, O 0.0013%), and the rest are Fe elements” in Example 1 are replaced with “C 0.5%, Si 0.3%, Mn 0.75%, Cr 1%, V 0.15%, Al 0.02%, impurities 0.0015% (including H 0.0002%, O 0.0013%), and the rest are Fe elements”, and the other steps are the same as in Example 1, and are recorded as “50CrVA-1”.

[0057] Comparative Example 2

[0058] The “C 0.51%, Si 0.32%, Mn 0.73%, Cr 0.99%, V 0.15%, Al 0.02%, Ti 0.019%, B 0.0031%, impurities 0.0014% (including H 0.0002%, O 0.0012%), and the rest are Fe elements” in Example 2 are replaced with “C 0.5%, Si 0.3%, Mn 0.75%, Cr 1%, V 0.15%, Al 0.02%, impurities 0.0014% (including H 0.0002%, O 0.0012%), and the rest are Fe elements”, and the other steps are the same as in Example 2, recorded as “50CrVA-2”.

[0059] Comparative Example 3

[0060] Traditional commercial spring steel 50CrVA purchased on the market.

[0061] Performance Test:

[0062] By using the end hardening test to detect the permeability of the spring steel materials obtained in Examples 1 to 2, it can be seen that the hardenability values ​​of Examples 1 to 2 are all J48 / 30, which is better than J49 / 21 of the commercial 50CrVA described in Comparative Example 3, that is, the hardenability of the spring steel material prepared by the present invention is significantly improved compared with the existing commercial spring steel 50CrVA.

[0063] The spring steel materials obtained in Examples 1-2 and Comparative Examples 1-2 were placed in simulated seawater (3.5 wt % NaCl aqueous solution) for potentiodynamic polarization test and open circuit potential test.

[0064] The potentiodynamic polarization comparison diagram of the spring steel material obtained in Example 1 and Comparative Example 1 is shown in Figure 2 As shown, the open circuit potential comparison diagram of the spring steel material obtained in Example 1 and Comparative Example 1 is as follows Figure 3 As shown. Combined Figure 2 and Figure 3 As shown, in the potentiodynamic polarization test, the self-corrosion potential of Example 1 is significantly higher than that of Comparative Example 1, and the corrosion current of Example 1 is always lower than that of Comparative Example 1 at the same potential in the anode region. In the 60-min open circuit potential experiment, the self-corrosion potentials of Example 1 and Comparative Example 1 (compared to SCE) both decrease with time, and the self-corrosion potential of Example 1 is higher than that of Comparative Example 1 throughout the process. The above results show that Example 1 has better corrosion resistance than Comparative Example 1.

[0065] The potentiodynamic polarization comparison diagram of the spring steel material obtained in Example 2 and Comparative Example 2 is shown in FIG. Figure 4 As shown, the open circuit potential comparison diagram of the spring steel material obtained in Example 2 and Comparative Example 2 is as follows Figure 5 As shown. Combined Figure 4 and Figure 5 As shown, in the potentiodynamic polarization test, the self-corrosion potential of Example 2 is close to that of Comparative Example 2, and the magnitude relationship between the two needs to be further determined by Tafel extrapolation. However, in the anode region, it can be clearly seen that the corrosion current of Example 2 is smaller at the same potential. In the 60-min open circuit potential experiment, the self-corrosion potentials of Example 2 and Comparative Example 2 (compared to SCE) both decrease with time, and the self-corrosion potential of Example 2 is higher than that of Comparative Example 2 throughout the process. The above results show that Example 2 has better corrosion resistance than Comparative Example 2.

[0066] The mechanical properties of the spring steel materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1;

[0067] The electrochemical corrosion properties of the spring steel materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were calculated by Tafel extrapolation method, and the results are shown in Table 1.

[0068] Table 1 Mechanical properties and electrochemical corrosion performance test results of spring steel materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3

[0069]

[0070] As can be seen from Table 1, by comparing Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, and Example 3 with Comparative Example 3, it can be known that the plastic extension strength of the spring steel materials obtained in Example 1, Example 2 and Example 3 is better than that in Comparative Example 1, Comparative Example 2 and Comparative Example 3, that is, the strength level of the spring steel materials obtained in Examples 1 to 3 is improved; the impact energy of the spring steel materials obtained in Example 1, Example 2 and Example 3 exceeds 30J, while the impact energy of the spring steel materials obtained in Comparative Example 1, Comparative Example 2 and Comparative Example 3 is less than 10J, that is, the technical solution of the present invention can ensure the high strength of the spring steel material while greatly improving its impact energy.

[0071] The variation of the solid solution amount of different elements in the high-strength, toughness and corrosion-resistant Cr-V spring steel prepared by the present invention with temperature is as follows: Figure 1 As shown. Figure 1 It can be seen that the multi-element coupling system in spring steel can be optimized and designed according to the change law, and the B element in the form of solid solution can be used to strengthen the effect of grain boundary and in-situ nano-carbide precipitation phase, so that the material can further optimize the hardenability and impact work on the basis of maintaining the original good comprehensive mechanical properties, and significantly improve the corrosion resistance of spring steel. Combined with the results shown in Table 1, the new component has a higher corrosion potential and a lower self-corrosion current. It can be seen that the technical solution of the present invention can significantly improve the corrosion resistance of spring steel materials, thereby avoiding corrosion damage of spring steel during storage and transportation in the marine atmospheric environment, and is more economical and practical than increasing the content of expensive elements such as Cr, Ni, and Mo.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-strength, tough and corrosion-resistant Cr-V spring steel based on multi-element coupling, characterized in that: It includes the following components in mass fraction: C 0.45-0.55%, Si 0.15-0.35%, Mn 0.60-0.90%, Cr 0.80-1.20%, V0.06-0.26%, Al 0.01-0.03%, Ti 0.015-0.025%, B0.0020-0.0055%, Nb 0-0.02%, P≤0.025%, S≤0.025%, Cu≤0.2%, Ni≤0.3%, N≤0.008%, impurities≤0.0017%, and the rest is Fe.

2. The method for preparing high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling according to claim 1, characterized in that: The steps include: Firstly, through multi-element coupled thermodynamic analysis, the trace element system and content in the steel are adaptively designed, and the metal blocks corresponding to the above elements are smelted in the order of C, Si, Mn, Cr, V, Al, Ti, B, Nb, P, S, Cu, Ni, N and Fe, and then cast, forged, quenched and tempered in sequence to obtain high-strength, toughness and corrosion-resistant Cr-V spring steel.

3. The method for preparing high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling according to claim 2 is characterized in that: The smelting temperature is 1600-1700° C., and the smelting time is 80-100 minutes.

4. The method for preparing high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling according to claim 3 is characterized in that: The forging temperature is 950-1000° C., the forging time is 15-25 minutes, and the total forging deformation is 5-9%.

5. The method for preparing high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling according to claim 3 or 4, characterized in that: The quenching temperature is 850-950° C., and the quenching medium is water or oil.

6. The method for preparing high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling according to claim 5, characterized in that: The tempering temperature is 450-550° C., and the tempering time is 80-100 minutes.

7. The method for preparing high-strength, toughness and corrosion-resistant Cr-V spring steel based on multi-element coupling according to claim 6, characterized in that: The plastic elongation strength R of the high-strength, tough and corrosion-resistant Cr-V spring steel obtained p0.2 ≥1250MPa, tensile strength R m ≥1300MPa, elongation after fracture A≥10%, end quenching index J≥48HRC / 30, impact energy≥30J.

Citation Information

Patent Citations

  • Black-scale spring flat steel rolling technological method

    CN106555115A

  • A high-strength corrosion-resistant spring steel and its preparation method

    CN114107841B